Induced sputum eicosanoid concentrations in asthma. - Pavord, I; Ward, R; Woltmann, G; Wardlaw, A; Sheller, JR; Dworski, R (1999)
Further definition of the role of leukotrienes (LT) and prostaglandins (PG) in asthma would be helped by a noninvasive method for assessing airway production. The supernatant from sputum induced with hypertonic saline and dispersed using dithiotrietol has been successfully used to measure other molecular markers of airway inflammation and might be a useful method. We have measured induced sputum supernatant LTC(4)/D(4)/E(4) concentrations using enzyme immunoassay and PGE(2), PGD(2), TXB(2), and PGF(2alpha) using gas chromatography-negative ion chemical ionization-mass spectroscopy in 10 normal subjects and in 26 subjects with asthma of variable severity. Sputum cysteinyl-leukotrienes concentrations were significantly greater in subjects with asthma (median, 9.5 ng/ml) than in normal control subjects (6.4 ng/ml; p < 0.02) and greater in subjects with persistent asthma requiring inhaled corticosteroids (median, 11.4 ng/ml) or studied within 48 h of an acute severe exacerbation of asthma (13 ng/ml) than in subjects with episodic asthma treated with inhaled beta(2)-agonists only (7.2 ng/ml). There were no significant differences in the concentrations of other eicosanoids between groups, although there was a negative correlation between the percentage sputum eosinophil count and sputum PGE(2) concentration (r = -0.48; p < 0.01) in subjects with asthma. We conclude that induced sputum contains high concentrations of eicosanoids and that sputum LTC(4)/D(4)/E(4) concentrations are significantly greater in subjects with asthma than in normal subjects. The inverse relationship between eosinophilic airway inflammation and sputum PGE(2) concentration would be consistent, with the latter having an anti-inflammatory role.